2015
DOI: 10.1002/adma.201502569
|View full text |Cite
|
Sign up to set email alerts
|

Flexography‐Printed In2O3 Semiconductor Layers for High‐Mobility Thin‐Film Transistors on Flexible Plastic Substrate

Abstract: uniform, continuous and dense layers and is thus more suitable for printed TFTs with larger channel dimensions. Several precursor routes for solution-processed metal-oxide semiconductor layers based on metal alkoxides, [ 14,15 ] and on metal salts such as acetates, nitrates, and chlorides have been reported. [ 16,17 ] Precursors based on metal nitrates have been shown to convert into metal oxides generally at lower temperatures than acetateor chloride-based precursors. [ 17,18 ] In contrast to metal alkoxides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
111
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 43 publications
6
111
0
Order By: Relevance
“…83 Recently, promising results of the first roll-to-roll compatible fabrication of In 2 O 3 patterns on PI substrates via flexographic printing have also been demonstrated. 250 f. Device configuration. The majority of the reported flexible n-type solution-processed metal oxide semiconductor TFTs are fabricated in BG staggered configuration with only few devices in BG coplanar, 145,196 TG staggered, 226 or TG coplanar setup.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…83 Recently, promising results of the first roll-to-roll compatible fabrication of In 2 O 3 patterns on PI substrates via flexographic printing have also been demonstrated. 250 f. Device configuration. The majority of the reported flexible n-type solution-processed metal oxide semiconductor TFTs are fabricated in BG staggered configuration with only few devices in BG coplanar, 145,196 TG staggered, 226 or TG coplanar setup.…”
mentioning
confidence: 99%
“…. 191,[193][194][195][196][197]200,220,221,[223][224][225]250 (III) The third and last group presents a few examples of devices with l FE ! 10 cm 2 V À1 s…”
mentioning
confidence: 99%
“…Most recently, Alastalo et al reported flexography-printed In 2 O 3 semiconductor layers for high-mobility thin-film transistors on flexible plastic substrate. Indium nitrate salt in 2ME was used as precursor solution [20]. The printing process resulted in an enhancement-mode In 2 O 3 TFTs on ALD-grown amorphous A l2 O 3 with a mobility value, P sat | 8 cm 2 /Vs.…”
Section: Printed Metal Oxide Tftsmentioning
confidence: 99%
“…Only a dedicated processing technology and reduced thickness of oxide dielectrics [ 17 ] allows preparing radiation hard CMOS components withstanding 100 krad(Si), as necessary for example for space applications. [ 8,20 ] Importantly, HMSO can be considered an intrinsically stable semiconducting material class due to the high formation energy of the oxide based ionic lattice and their amorphous structure. HMSOs already fi nd commercial application in displays as they combine outstanding electronic transport properties with transparency.…”
Section: Introductionmentioning
confidence: 99%